Profiling children longitudinally: A three‐year follow‐up study of perceived and actual motor competence and physical fitness. (19th April 2021) - Estevan, Isaac; Menescardi, Cristina; García‐Massó, Xavier; Barnett, Lisa M.; Molina‐García, Javier
Abstract : Longitudinal designs enhance our understanding of children's development and its influence on movement behaviors and health. This three‐year follow‐up study aimed to develop profiles according to perceived and actual motor competence (MC) (locomotion, object control, and overall) and physical fitness in boys and girls longitudinally including children's temporal migrations among clusters in terms of profiling trends. A secondary aim was to compare physical activity participation and weight status at each time point according to these profiles. One hundred and four typically developing Spanish children (45.8% girls) between 4 and 9 years old at baseline participated in this study. Data were collected at three time points one year apart, between January 2016 and May 2018. A self‐organizing map and K ‐means cluster analysis were used to classify and visualize the values and temporal trajectories longitudinally. The study of the profiles in three consecutive years revealed five profiles, three for boys [ie, profile 1 ( aligned—high ), profile 2 ( aligned‐partially—low perception‐medium actual MC and fitness ), and profile 3 ( non‐aligned—medium perception‐low actual MC and fitness )]; and two for girls [ie, profile 4 ( aligned—high ) and profile 5 ( aligned—low )]. For highly perceived and capable children, boys (profile 1) and girls (profile 4), there was a tendency for higher physical activity participation and lower body mass index and waist circumference over time compared to their counterparts who had medium and/or low levels in perception and actual MC and fitness ( P  < .05). As children age, those with low values in perceived and actual MC and fitness in object control skills will present a higher probability of maintaining unhealthy lifestyles. So, prior intervention, children's profiles identification should be analyzed according to the type of MC.